2011
DOI: 10.3109/09593985.2011.601804
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the reliability and validity of the measurement of elderly people's clinical walking speed: A systematic review

Abstract: The number of available walking tests has increased dramatically over the past decades. Therefore, it is highly important to help clinicians choose the most appropriate walking test for a specific setting. This systematic review aimed to critically evaluate the reliability, validity, and responsiveness of clinical walking speed in a broad population of elderly persons living in the community, sheltered housing, or institutions. Literature searches were performed in several different databases. Key words were b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
102
2
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 106 publications
1
102
2
11
Order By: Relevance
“…Procedures differ in regards to distance (2 meters to 40 meters) (Rydwik et al, 2012), start (static versus dynamic) (PhanBa et al, 2012), path (straight versus turn) (van Herk, Arendzen, & Rispens, 1998), speed (self-selected versus maximal) (Rydwik et al, 2012), instruction (e.g. "walk at a comfortable pace" versus " walk as if you are taking a stroll through the park") (Nascimento et al, 2012), and timing instrument (e.g.…”
Section: Recommendations On Assessment Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Procedures differ in regards to distance (2 meters to 40 meters) (Rydwik et al, 2012), start (static versus dynamic) (PhanBa et al, 2012), path (straight versus turn) (van Herk, Arendzen, & Rispens, 1998), speed (self-selected versus maximal) (Rydwik et al, 2012), instruction (e.g. "walk at a comfortable pace" versus " walk as if you are taking a stroll through the park") (Nascimento et al, 2012), and timing instrument (e.g.…”
Section: Recommendations On Assessment Proceduresmentioning
confidence: 99%
“…The White Paper: "Walking Speed: the Sixth Vital Sign" published in 2009 consolidated available evidence on a robust measure, walking speed (Adell, Wehmhorner, & Rydwik, 2013;Afilalo et al, 2010;Castell et al, 2013;Graham, Fisher, Berges, Kuo, & Ostir, 2010;Peters, Fritz, & Krotish, 2013;Quach et al, 2011;Rydwik, Bergland, Forsen, & Frandin, 2012;Shimada et al, 2013;Verghese, Wang, & Holtzer, 2011). Since publication of the original article, evidence has emerged regarding updated recommendations on testing protocols.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a quick and easy measure and is not limited to specific equipment. Furthermore, it is a valid, sensitive, and specific measure with high inter-rater and testretest reliability (Bellet et al 2012;Munoz-Mendoza et al 2011;Nasuti et al 2013;Rydwik et al 2012). Currently, there are many methods to assess walking speed varying in pace (i.e., normal or as fast as possible), static or dynamic start, and walking distance or time.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed conflicting results regarding methodologically induced variance in assessed walking speed in elderly (Ng et al 2013;Peters et al 2013). This hampers comparison of the different studies and may affect the clinical interpretation of walking speed (Graham et al 2008b;Rydwik et al 2012).…”
Section: Introductionmentioning
confidence: 99%